ENVIRONMENTAL EXPOSURES TO LOW LEVEL OF CADMIUM AND LEAD AND HEARING IMPAIRMENT IN IRAQI PATIENTS - Al-khfajy, Wrood S; Baiee, Ghadeer Kadhum; Arif, Inam Sameh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: We examined the relations between blood cadmium and lead exposure and hearing impairments in the Iraqi people. Methods: We analyzed data from 51 individual 13â€“75 ages who had been randomly dispensed to the audiometry examination center at Al-Hilla Teaching Hospital (Babel) for each Iraqi civilian who said, I suffering from the hearing problem.â€ Pure-tone average (PTA) of auditory thresholds at frequencies of 0.5, 1, 2, and 4 kHz was calculated, and hearing impairment was described as a PTA >25 dB in either ear. Results: All patients who suffer from hearing impairment have serum lead level (23.14Â±1.76 Î¼g/dL), which is a significantly elevated in comparison to control group (21.20Â±2.08 Î¼g/dL). In addition to lead, the blood level of cadmium in people with hearing impairment was showed a significant elevation (0.28Â±0.05 Î¼g/dL) in comparison to normal people (0.22Â±0.03 Î¼g/dL). In general, this elevation remains within normal reference for the blood level of cadmium (0.5 Î¼g/dL). Conclusions: The present study revealed that the environmental and occupational cadmium and lead coexposures lead to a significant elevation in the blood level of these metals and could have an essential part in the progression of hearing loss.